La resiliencia, en la ansiedad por el aislamiento preventivo de la pandemia covid-19, en los moradores del barrio “Daniel Álvarez Burneo” de la ciudad de Loja, periodo 2020-2021. - Espinosa Palacios, Ivana Alejandra (2022)
In the present investigation, a compilation of information was carried out on the study variables, these being resilience and anxiety, with the aim of identifying the influence of Resilience, in the management of Anxiety due to the Preventive Isolation of the COVID-19 Pandemic., in the residents of the "Daniel Álvarez Burneo" neighborhood of the City of Loja, during the period 2020-2021, of a descriptive, explanatory and propositional type, with a non-experimental field design, with a mixed approach, applying the use of the methods Quantitative, Qualitative, Analytical-Synthetic, Descriptive, Deductive - Inductive, Hermeneutic and Statistical in a population sample of 25 families, of which it was obtained as a result that most of the residents present a high degree of anxiety due to the preventive isolation generated by the COVID-19 pandemic, demonstrating a low level of resilience, for which these results were evidenced through the application of instruments, such as: the psychological reagents (Wagnild and Young Resilience Scale (ER) and the Beck Anxiety Inventory (BAI)) and on the other hand the interview and survey. For this reason, it is considered important to make use of the alternative proposal proposed in this project and intervene in a timely manner, in order to improve the quality of life of each of the residents. Keywords: Resilience, Pandemic, Covid-19, Preventive Isolation, Anxiety.